1994
DOI: 10.1007/bf01876650
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced autofluorescence for medical diagnosis

Abstract: The naturally occurring autofluorescence of cells and tissues is based on biomolecules containing intrinsic fluorophores, such as porphyrins, the amino acids tryptophan and tyrosine, and the coenzymes NADH, NADPH, and flavins. Coenzymes fluoresce in the blue/green spectral region (fluorecence lifetimes: 0.5-6 ns) and are highly sensitive indicators of metabolic function. Steadystate and time-resolved blue-green autofluorescence is, therefore, an appropriate measure of the function of the respiratory chain as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(133 citation statements)
references
References 79 publications
(74 reference statements)
6
118
0
3
Order By: Relevance
“…35 Porphyrins and metalloporphyrins typically have absorption maxima between 398 and 421 nm and emission maxima between 530 and 633 nm. 24 Because porphyrins are produced by bacterial metabolic activity, the red fluorescence intensity reflects the intensity and extent of the caries-affected tissues. Spectrographic studies have shown that carious dentine fluoresces more intensely in the red portion of the visible spectrum than healthy dentine.…”
Section: Introductionmentioning
confidence: 99%
“…35 Porphyrins and metalloporphyrins typically have absorption maxima between 398 and 421 nm and emission maxima between 530 and 633 nm. 24 Because porphyrins are produced by bacterial metabolic activity, the red fluorescence intensity reflects the intensity and extent of the caries-affected tissues. Spectrographic studies have shown that carious dentine fluoresces more intensely in the red portion of the visible spectrum than healthy dentine.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the question is if the fluorescence is due to the porphyrin content or some other constituent. However, it has been shown that the spectra from red fluorescing bacteria is very similar to the emission spectra of porphyrins [3,4,16].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few publications so far about bacteria associated with periodontal disease and their ability to emit red fluorescence thus, and it is of interest to investigate which periodontopathogens that are able to emit red fluorescence since according to the literature this property could be used for diagnosis and treatment [3,4,16]. To our knowledge there are no specific studies on the fluorescence of A. actinomycetemcomitans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that this linear relationship is a calibration curve for PA14/EFGP only. Other strains of PA or other bacterial species would most likely yield a different calibration curve that would have to be obtained prior to any quantification experiments, especially if the stains are not tagged with a fluorophore similar to EFGP, and quantification relies on only the autofluorescence of NADH [55]. Thus, this method has limitations at high CFU counts, where fluorescence intensity may not correlate to a linear curve.…”
Section: Fluorescence Spectroscopy As a Tool To Quantify The Planktonmentioning
confidence: 99%